Utilization of non-pharmacological methods and the perceived barriers for adult postoperative pain management by the nurses at selected National Hospitals in Asmara, Eritrea - Betiel Yihdego Kidanemariam; Traudl Elsholz; Laban L. Simel; Eyasu H. Tesfamariam; Yonatan Mehari Andemeskel (BMC, 2020)
Abstract Background Pharmacological methods are widely used for postoperative pain management however, poorly controlled pain continues to pose a significant challenge. Non pharmacological methods could contribute to the unresolved postoperative pain management in assisting nurses' routine care and reducing the need for medication. This study aimed to assess nurses' utilization of non-pharmacological methods in postoperative pain and the perceived barriers for their implementation at the National Hospitals. Methods This was a descriptive cross sectional study conducted among 154 nurses working at the National Referral Hospitals and Sembel Private Hospital. A standardized five-point Likert-scale questionnaire which assesses nurses' utilization of selected non-pharmacological methods and the perceived barriers for the implementation was used to collect data. Descriptive statistics for the demographic data, independent samples t-test, one way ANOVA and factorial ANOVA were used to analyze the data. Statistical significance level was set at P < 0.05. Results The study found out that emotional support (45.5%), helping with daily activities (67.5%) and creating a comfortable environment (61%) were mostly used while, cognitive-behavioral (5.9%) and physical methods (5.8%) were hardly used. The results also showed that, characteristics such as, age (p = 0.013), level of education (p = 0.012), work experience (p = 0.001) and place of work (p = 0.001), were significantly related to the use of non-pharmacological methods at bivariate level. However, hospitals were the only determinants of the non-pharmacological methods at multivariable level with a statistical significance of (p < 0.001). On the perceived barriers; heavy work load (87.7%), shortage of time (84.4%), limited resources (82.5%), deficit in the guidelines for pain management (77.3%), patient's uncooperative behavior (57.1%), language difference (64.4%), nurse's lack of knowledge (50%) and experience (40.3%) were identified. Conclusion The use of non-pharmacological methods in the studied hospitals varied greatly due to knowledge and experience of the nurses. Therefore, it is recommended that exposure and training for all health care providers at all level is a paramount importance in order to appreciate the benefits of non-pharmacological methods applicable to postoperative pain management. This could be achieved through on job training, seminars, scientific conferences and other brainstorming forums.